Impact of innovation and implementation of technology in a film company in the city of Cajamarca, 2024 - Barinotto Roncal, Patricia; Arribasplata Sánchez, Erica Pamela; Huamán Chuquilín, Kelly Allison; Infante Pollack, Wilmer Enrique (LACCEI, 2025)
The objective of this research work is to identify the influence of innovation and implementation of technology in a Cinematographic company, in the city of Cajamarca, 2024. The innovation and implementation of technology within organizations and in Peru is in decline due to the different circumstances that we have gone through, investment in technology and the increase in innovation in organizations in the country has remained scarce, and this means that research in these areas is not promoted in the appropriate way, hence I could say that Peru has cases of economic means for change and applied sciences. This research is of a descriptive type with a nonexperimental and cross-sectional design, with a study population of infinite participants from film companies and with a probabilistic sample of 245. Surveys were used as a data collection technique. Finally, the result was that the implementation of technology reaches 66.9%, which indicates a significant degree of dependence between the use of innovation and technological implementation in the year 2024, where innovation influences the perception of security and privacy by 59.8%, compatibility with clients by 58.1%, and facilitators by 52.3%. In summary, the purpose of this exploration is to determine the effect that technological implementation has, its importance and innovation within Peruvian organizations.